The Fundamentals of Modern Astrophysics A Survey of the Cosmos from the Home Planet to Space Frontiers - Marov, Mikhail Ya (Springer New York : Imprint: Springer, 2015)
The Fundamentals of Modern Astrophysics provides an overview of the modern science of astrophysics. It covers the Sun, Solar System bodies, exoplanets, stars, and star life cycle, planetary systems origin and evolution, basics of astrobiology, our galaxy the Milky Way, other galaxies and galactic clusters, a general view of the Universe, its structure, evolution and fate, modern views and advanced models of cosmology as well as the synergy of micro- and macro physics, standard model, superstring theory, multiversity and worm holes. The main concepts of modern astrophysics and prospects for future studies are accompanied by numerous illustrations and a summary of the advanced projects at various astronomical facilities and space missions. Dr. Marov guides readers through a maze of complicated topics to demystify the field and open its wonders to all.